Silicone Foley’s catheter as an effective alternative to Hunter’s rod in staged flexor tendon reconstruction of the hand - Tawheed Ahmad; Sheikh Adil Bashir; Mohammad Inam Zaroo; Adil Hafeez Wani; Saima Rashid; Summaira Jan (Indian Journal of Plastic Surgery)
Context: Staged flexor tendon reconstruction is most suitable treatment method for extensive zone II tendon injuries. The Hunter’s rod used in this procedure is costly and not easily available, which adds to the miseries of both patients as well as treating surgeon. Aims: The aim of this study is to evaluate the results of staged zone II flexor tendon repair using silicone Foley’s catheter as a cheaper and readily available alternative to Hunter’s rod. Settings and Design: This was a prospective study. Materials and Methods: Seventy digits in 35 patients were treated by the staged flexor tendon reconstruction using silicone Foley’s catheter in place of Hunter’s rod, and the patients were followed for an average period of 18 months. Early controlled motion exercise protocol was instituted in all cases. Results: As per the Strickland scale, total active motion obtained was excellent in 70%, good in 20%, fair in 7.1% and poor in 2.9% of patients. Conclusions: Silicone Foley’s catheter is cheaper, easily available and an effective alternative to Hunter’s rod in staged flexor tendon reconstruction procedure, yielding high rates of excellent and good results with fewer complications.